Sustained Regression of Hydroxycarbamide Induced Actinic Keratoses after Switching to Anagrelide - Georgios Gaitanis; Dora Gougopoulou; Eleni Kapsali; Ioannis D. Bassukas (Case Reports in Dermatological Medicine)
Hydroxycarbamide (HC) is the first-line treatment for certain myeloproliferative neoplasms, such as polycythemia vera and essential thrombocytosis (ET). In a subset of these patients long-term treatment with HC can result in the development of confluent actinic keratoses (AK) followed by invasive keratinocytic carcinomas (“squamous dysplasia”), preferentially on sun-exposed skin. Discontinuation or dose reduction of HC may result in partial improvement. A 59-year-old farmer after 14 years on HC (2 gr/d) and acetylsalicylic acid (100 mg/d) for ET, was referred for numerous, hyperkeratotic AK on face, scalp, and hands that could not be controlled with repeated (N=15) cryosurgery sessions in the previous 3 years. Acitretin (0.32 mg/kg daily) and topical treatments (cryosurgery with ingenol mebutate) were initiated with only marginal improvement after 3 months. Acitretin dose was doubled and HC was switched to anagrelide (0.5 mg twice daily). Within a month the AK load regressed significantly and, at 3 months follow-up, complete clinical remission was achieved and acitretin was discontinued. Twenty months later the patient is clear from AK. In conclusion, the impressive and sustainable AK remission under anagrelide draws attention to a possible role of the phosphodiesterase 3 pathway, the major pharmacological target of anagrelide, as a potential therapeutic target for keratinocytic cancers.